Faculty Participation in Planning Activities and it's Relationship with their Vision of the Institution - Juan José Sevilla García; Jesús Francisco Galaz Fontes; José Luis Arcos Vega (Universidad Autónoma de Baja California, 2008)
This work took place among academicians in a public state university, it analyzes the posible relation of the academicians' level of participation in the formulation process of the Comprehensive Institucional Strengthening Program (Programa Integral de Fortalecimiento Institucional, PIFI, in Spanish) and/or the Program for Strengthening High Education Institutions (Programa de Fortaleciemiento de la Dependencia de Educación Superior, PRODES, also in Spanish), with their level of information, their perception of the working environment, administration, decision-making and influence, institutional image and sense of belonging, and work satisfaction. The information used for this analysis was provided by the Organizational Environment Annual Survey (Encuesta Anual de Ambiente Organizacional, EAAO, name in Spanish), which is applied every year to said institution. Results show that academicians who have higher levels of participation also appear to have, in general, a better image of the institution, particularly regarding working environment, level of information and decision-making. Also, those who have a better perception of the institution's administration, image and pride as well as work satisfaction appear to have higher levels of participation, though the difference is minor. These results are discussed according to the value that the strategic and contextual planning gives to the actors of the organization.